2021
DOI: 10.3390/antibiotics10111417
|View full text |Cite
|
Sign up to set email alerts
|

Global Spread and Molecular Characterization of CTX-M-Producing Salmonella Typhimurium Isolates

Abstract: This study aimed to determine the global prevalence and molecular characterization of CTX-M-producing Salmonella Typhimurium isolates. A total of 330 (15.2%, 330/21779) blaCTX-M-positive S. Typhimurium were obtained from the public databases in July 2021. Thirteen variants were found in the 330 members of the blaCTX-M group, and blaCTX-M-9 (26.4%, 88/330) was the most prevalent. The majority of blaCTX-M-positive S. Typhimurium were obtained from humans (59.7%, 197/330) and animals (31.5%, 104/330). The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…23 The main mechanisms underlying resistance to third-generation cephalosporins in Salmonella have been attributed to extended-spectrum β-lactamase (ESBL) genes obtained via horizontal transfer, and CTX-M enzymes include the most common ESBLs that are prevalent worldwide. 41 A previous study by our team showed that the rate of ESBL gene detection in our hospital was 16.38%, and CTX-M was the most common ESBL gene. 42 Our report suggested a continuous and slow increase in the rate of resistance to some antimicrobial agents, with only a significant increase in the rate of resistance to ciprofloxacin in 2013 because the CLSI lowered the ciprofloxacin susceptibility breakpoints in 2013, with the new MIC being applied only to Salmonella spp.…”
mentioning
confidence: 72%
“…23 The main mechanisms underlying resistance to third-generation cephalosporins in Salmonella have been attributed to extended-spectrum β-lactamase (ESBL) genes obtained via horizontal transfer, and CTX-M enzymes include the most common ESBLs that are prevalent worldwide. 41 A previous study by our team showed that the rate of ESBL gene detection in our hospital was 16.38%, and CTX-M was the most common ESBL gene. 42 Our report suggested a continuous and slow increase in the rate of resistance to some antimicrobial agents, with only a significant increase in the rate of resistance to ciprofloxacin in 2013 because the CLSI lowered the ciprofloxacin susceptibility breakpoints in 2013, with the new MIC being applied only to Salmonella spp.…”
mentioning
confidence: 72%
“…variety of first-line drugs such as ampicillin, chloramphenicol and co-trimoxazole (5). Therefore, an appropriate molecular typing method should be used in combination with serotyping to investigate the epidemiology of Salmonella.…”
Section: Multi-locus Sequence and Drug Resistance Analysis Of Salmone...mentioning
confidence: 99%
“…Salmonella serotypes are typically associated with their host adaptation and virulence capability, rendering serotyping to be a key tool for Salmonella surveillance and outbreak investigations ( 4 ). However, treatment of invasive salmonellosis has been compromised due to the emergence of Salmonella strains that are resistant to a variety of first-line drugs such as ampicillin, chloramphenicol and co-trimoxazole ( 5 ). Therefore, an appropriate molecular typing method should be used in combination with serotyping to investigate the epidemiology of Salmonella .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the clinical importance of nasal carriage of CTX-M-producing E. coli might be underestimated. Although horizontal transfer is the main reason for bla CTX-M dissemination, clonal spread of bla CTX-M -harbouring strains, such as E. coli ST8369 in this study, CTX-M-15-producing E. coli ST949 in water surfaces, E. coli ST2179 encoding CTX-M-65 in retail meat, and bla CTX-M-transmission of bla CTX-M in E. coli and Salmonella from various sources (Chen et al, 2021;Guo and Zhao, 2021;Yang et al, 2014;Nadimpalli et al, 2019;Zhang et al, 2021;Zeng et al, 2021). In this study, various plasmids such as IncHI2, IncK1, IncX1, and IncI1 were associated with bla CTX-M .…”
Section: Discussionmentioning
confidence: 74%
“…Horizontal transfer mediated by plasmids and mobile elements is responsible for the global spread of bla CTX-M ( Bevan et al., 2017 ; Partridge et al., 2018 ). For example, IncI, IncFII, and IncHI2 plasmids facilitate the horizontal transmission of bla CTX-M in E. coli and Salmonella from various sources ( Chen et al., 2021 ; Guo and Zhao, 2021 ; Yang et al., 2014 ; Nadimpalli et al., 2019 ; Zhang et al., 2021 ; Zeng et al., 2021 ). In this study, various plasmids such as IncHI2, IncK1, IncX1, and IncI1 were associated with bla CTX-M .…”
Section: Discussionmentioning
confidence: 99%